2021
DOI: 10.3390/cryst11111381
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Processing of a Mg-Zn-Ca Alloy by Equal-Channel Angular Pressing for Use in Biodegradable Implants for Osteoreconstruction

Abstract: Widespread use of Mg-Zn-Ca alloys in clinical orthopedic practice requires improvement of their mechanical properties—in particular, ductility—and enhancement of their bioactivity for accelerated osteoreconstruction. The alloy was studied in two structural states: after homogenization and after equal-channel angular pressing. Immersion and potentiodynamic polarization tests showed that the corrosion rate of the alloy was not increased by deformation. The mass loss in vivo was also statistically insignificant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Previous in vivo studies have revealed that hydrogen gas evolution is primarily found adjacent to Mg–Zn–Ca implants investigated [ 17 , 32 , 39 , 43 , 44 , 148 , 149 ]. Although the composition and volume of the released gas during ZX00 alloy degradation were not investigated in this study, our μCT and histology findings after 6 weeks of implantation revealed numerous gas voids mainly in the intramedullary cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo studies have revealed that hydrogen gas evolution is primarily found adjacent to Mg–Zn–Ca implants investigated [ 17 , 32 , 39 , 43 , 44 , 148 , 149 ]. Although the composition and volume of the released gas during ZX00 alloy degradation were not investigated in this study, our μCT and histology findings after 6 weeks of implantation revealed numerous gas voids mainly in the intramedullary cavity.…”
Section: Discussionmentioning
confidence: 99%
“…A popular Mg-Zn-Ca alloying system [ 13 , 43 , 44 ] was chosen for the present study. After appropriate thermomechanical treatment, alloys of this kind have an excellent balance between mechanical and corrosion properties [ 45 , 46 , 47 , 48 , 49 ]. The alloy was cast from commercially pure components, and the chemical composition of the alloy-Mg-0.85Zn-0.15Ca-0.012 Zr (all in wt.%) was determined by the optical emission spectrometer ARL 4460 OES (ThermoFisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…One of the major concerns regarding the degradation of magnesium in biological applications is the accumulation of hydrogen gas, which is a by-product of corrosion. However, only one of the studies, in which the implants from an Mg–Zn–Ca alloy were inserted subcutaneously, reported the formation of gas under the skin [ 82 ]. A good biological response including bone formation around the implant was observed in pure magnesium and Mg–Ca and Mg–Sr alloys processed via ECAP [ 58 ] and via HPT [ 90 ].…”
Section: Biological Responsementioning
confidence: 99%
“… Corrosion rate reported in samples of magnesium processed via ECAP [ 52 , 55 , 56 , 57 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 69 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 82 , 83 , 84 , 85 , 86 , 87 ] and HPT [ 19 , 88 , 90 , 91 , 92 , 93 , 94 , 95 , 97 , 98 , 99 , 100 ] plotted as a function of the grain size. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation